2014
DOI: 10.1055/s-0034-1371755
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, Emotion, and Childhood Stuttering

Abstract: The purpose of this article is to provide a brief description of temperament and emotion, review empirical evidence pertaining to their possible association with childhood stuttering, and discuss possible clinical implications. In general, temperament is typically thought of as an individual's constitutionally (biologically) based behavioral proclivities. These proclivities often include emotional reactivity and self-regulation. Reactivity refers to arousal of emotions, motor activity, and attention, and self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 72 publications
0
32
1
Order By: Relevance
“…Recently, several empirical investigations have studied differences in temperament and emotions between children who stutter (CWS) and children who do not stutter (CWNS), as well as the impact of emotional processes on stuttering frequency (e.g., Eggers, De Nil, & Van den Bergh, 2010;Jones, Buhr, et al, 2014;Karrass et al, 2006;Walden et al, 2012). Reviews of these studies (Conture, Kelly, & Walden, 2013;Jones, Choi, Conture, & Walden, 2014;Kefalianos, Onslow, Block, Menzies, & Reilly, 2012) suggest that there is an association between aspects of emotion and childhood stuttering. For example, CWS, compared to CWNS, exhibit: (a) less adaptability (e.g., Anderson, Pellowski, Conture, & Kelly, 2003;Schwenk, Conture, & Walden, 2007) and (b) more negative affect/mood (e.g., Ntourou, Conture, & Walden, 2013).…”
Section: Emotion and Stutteringmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, several empirical investigations have studied differences in temperament and emotions between children who stutter (CWS) and children who do not stutter (CWNS), as well as the impact of emotional processes on stuttering frequency (e.g., Eggers, De Nil, & Van den Bergh, 2010;Jones, Buhr, et al, 2014;Karrass et al, 2006;Walden et al, 2012). Reviews of these studies (Conture, Kelly, & Walden, 2013;Jones, Choi, Conture, & Walden, 2014;Kefalianos, Onslow, Block, Menzies, & Reilly, 2012) suggest that there is an association between aspects of emotion and childhood stuttering. For example, CWS, compared to CWNS, exhibit: (a) less adaptability (e.g., Anderson, Pellowski, Conture, & Kelly, 2003;Schwenk, Conture, & Walden, 2007) and (b) more negative affect/mood (e.g., Ntourou, Conture, & Walden, 2013).…”
Section: Emotion and Stutteringmentioning
confidence: 99%
“…Comparatively less decrease, maintenance, or increase of RSA during speaking tasks may index a greater degree of emotion regulation and hence facilitate an individual's ability to engage in social communication as well as increase and/or maintain speech fluency. Children who stutter, when compared to their CWNS peers, exhibit greater emotion reactivity and lower regulation as indexed by caregiver report and behavioral (for review, see Jones, Choi, et al, 2014) and physiological measures (e.g., lower baseline RSA; Jones, Buhr, et al, 2014). Thus, it is quite possible that CWS, relative to CWNS, are at higher risk of initiating and/or maintaining a physiological response that is less supportive of fluent speech-language and more supportive of an emotionally reactive, fight/flight response.…”
Section: Hypothesis 3: For Cws Compared To Cwns Greater Decreases Imentioning
confidence: 99%
“…We are informed by the literature on young children's awareness of stuttering (Ambrose & Yairi, 1994; Boey, Van de Heyning, Wuyts, Heylen, Stoop, & Reinhard, 2009; Ezrati-Vinacour, Platzky, & Yairi, 2001), their development of negative communicative attitudes as a result of stuttering (Vanryckeghem, Brutten, & Hernandez, 2005), and their temperaments which account for individual differences in their reactivity and regulation (review in Jones, Choi, Conture, & Walden, 2014). Together, this empirical base illuminates potential connections between perceived competence, perceived social acceptance, and stuttering.…”
Section: Introductionmentioning
confidence: 99%
“…Children with high self-regulatory abilities tend to have high-quality social interactions, resilience when faced with adversity, and high academic achievement (Eisenberg, et al, 1997; Masten & Coatsworth, 1998; Rubin, Coplan, Fox, & Calkins, 1995). Importantly, extant research on the temperament characteristics of CWS have identified that CWS tend to have greater negative affect, differences in attentional processes, and lower adaptability than typically fluent peers (review in Jones, Choi, Conture, & Walden, 2014). Given that high self-regulatory abilities are associated with high achievement and competence, and that CWS, as a group, tend to demonstrate low self-regulatory abilities, it seems reasonable to speculate that CWS may be at risk for low perceived competence when compared to their typically fluent peers.…”
Section: Introductionmentioning
confidence: 99%
“…However, no single variable provides predictive ability to differentiate at the individual level that children will or will not recover from stuttering. At present, the data suggest that these factors should be viewed as potential risk factors and should be weighed together with other potential factors like language dissociations (Anderson, Pellowski, & Conture, 2005;Clark, Conture, Walden, & Lambert, 2015;Coulter, Anderson, & Conture, 2009), family history of stuttering (Kraft & Yairi, 2012), and the goodness of fit between temperament and environmental contexts Jones, Choi, Conture, & Walden, 2014).…”
mentioning
confidence: 99%